Different Photochemical Events of a Genetically Encoded Phenyl Azide Define and Modulate GFP Fluorescence1. Issue 23 (25th April 2013) - Reddington, Samuel C.; Rizkallah, Pierre J.; Watson, Peter D.; Pearson, Rachel; Tippmann, Eric M.; Jones, D. Dafydd
<x xml:space="preserve">Abstract</x> Expanding the genetic code opens new avenues to modulate protein function in real time. By genetically incorporating photoreactive phenyl azide, the fluorescent properties of green fluorescent protein (GFP) can be modulated by light. Depending on the residue in GFP programmed to incorporate the phenyl azide, different effects on function and photochemical pathways are observed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>